Sourcing Pandemic News: A Cross-National Computational Analysis of Mainstream Media Coverage of COVID-19 on Facebook, Twitter, and Instagram. Issue 9 (21st October 2021) - Mellado, Claudia; Hallin, Daniel; Cárcamo, Luis; Alfaro, Rodrigo; Jackson, Daniel; Humanes, María Luisa; Márquez-Ramírez, Mireya; Mick, Jacques; Mothes, Cornelia; I-Hsuan LIN, Christi; Lee, Misook; Alfaro, Amaranta; et al.
Abstract: This article explores the uses of sources in coverage of the COVID-19 pandemic in social media posts of mainstream news organizations in Brazil, Chile, Germany, Mexico, Spain, the U.K., and the U.S. Based on computational content analysis, our study analyzes the sources and actors present in more than 940, 000 posts on COVID-19 published in the 227 Facebook, Instagram, and Twitter accounts of 78 sampled news outlets between January 1 and December 31 of 2020, comparing their relative importance across countries, across media platforms, and across time as the pandemic evolved in each country. The analysis shows the dominance of political sources across countries and platforms, particularly in Latin America, demonstrating a strong role of the state in constructing pandemic news and suggesting that mainstream news organizations' social media posts maintain a strong elite orientation. Health sources were also prominent — consistent with the defining role of biomedical authority in health coverage—, while significant diversity of sources, including citizen sources, emerged as the pandemic went on. Our results also revealed that the use of specific sources significantly varied over time. These variations tend to go hand in hand with specific global milestones of the pandemic.